Replication Data for: Davvisámi earutkeahtes oamasteapmi ... - Janda, Laura A; Antonsen, Lene (DataverseNO, 2020)
This data shows the correlation analysis for our study with this description: On the basis of corpus data (9.5M words 1997-2010) we claim that North Saami is developing a grammatical distinction between alienable and inalienable possession. In previous work we documented a language change in North Saami in which the possessive suffix (“SOG”) as in girjji-id-easkka [book-ACC.PL-3PL] ‘their books’ is being replaced by an analytic construction with the reflexive genitive ieža-form, as in iežaska girjjiid ‘their books’. According to typologists, alienable/inalienable distinctions arise primarily in small languages where a language change takes place, and inalienability is marked by the synthetic construction. North Saami possessive constructions comport with these features, and SOG tends to mark inalienable possession, as opposed to the more neutral and widespread ieža-form. Statistical analysis shows that word frequency cannot account for the distribution of SOG vs. ieža-form, justifying focus on semantics. ...